As relações retóricas estabelecidas pelo conectivo e no texto visão de Túndalo (século XIII-XIV) - Limonta, Simone Morais (2012)
The objective from this work is to propose an investigation from the relations established by E on archaic Portuguese corpus. The specific objectives are to analyze how often each relation occurs, if there are other marks that accompany each formal relation and analyze the position of the nucleus and satellite. The hypothesis is that the connective E establish various rhetorical relations, so, we based our work on the following steps: we did a survey of how many times each relations occurred in the text, we observe the position of the nucleus and satellite present in relations and observe if there are other words or expressions that accompany the E in grammatical structure and help to establish the relation type. As a result, we observe that the text emerge relations Sequence, List, Contrast, Result, Cause, Motivation and Purpose. The Sequence and List occur in greater numbers than the rest. The position of the nucleus and the satellite keep the same according to the type of relationship, and those relation, not only the result showed, in all instances had formal marks that helped define it. These results indicate that since the language archaic period E establishes the connective relationships that go beyon the rhetorical List and Sequence, even though these two relationships are the most recurrent. This fact reaffirms that E is a very strong in link sequence and lists portions of text.